2022
DOI: 10.3390/polym14040708
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation and Cost–Benefit Analysis of Recycled Tire Polymer Fiber-Reinforced Cemented Paste Backfill

Abstract: To alleviate the environmental problems caused by scrap tire and tailings disposal, the performance of recycled tire polymer fiber (RTPF)-reinforced cemented paste backfill (CPB) was investigated. Ordinary CPB, commercial poly-propylene fiber (CPPF) and reinforced CPB were also investigated for comparison. Slump tests, unconfined compression tests and a cost–benefit analysis were conducted. The results indicate that the flowability of the RTPF-reinforced CPB decreased with the increasing fiber content. The fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Textile fibers derived from ELT can also act as substitutes for polymeric/synthetic fibers such as carbon [ 81 ], PVA [ 82 ], PP [ 83 ], polyethylene (PE) [ 84 ], and steel [ 81 ] in cement-based materials. These options received increasing attraction to resolve some of the environmental problems caused by waste tires, as well as improving the performance and durability of cement-based materials [ 38 , 39 , 85 , 86 ]. Long-term durability and performance of cement composites can be deteriorated by plastic shrinkage cracking caused by self-desiccation and external drying, especially for applications having large surface areas such as slabs on grade, thin surface repairs, patching, tunnel linings, etc.…”
Section: Reinforced Concretementioning
confidence: 99%
“…Textile fibers derived from ELT can also act as substitutes for polymeric/synthetic fibers such as carbon [ 81 ], PVA [ 82 ], PP [ 83 ], polyethylene (PE) [ 84 ], and steel [ 81 ] in cement-based materials. These options received increasing attraction to resolve some of the environmental problems caused by waste tires, as well as improving the performance and durability of cement-based materials [ 38 , 39 , 85 , 86 ]. Long-term durability and performance of cement composites can be deteriorated by plastic shrinkage cracking caused by self-desiccation and external drying, especially for applications having large surface areas such as slabs on grade, thin surface repairs, patching, tunnel linings, etc.…”
Section: Reinforced Concretementioning
confidence: 99%
“…Yu et al [12] studied the performance of recycled tire polymer fiber (RTPF) to strengthen the cementing paste backfill (CPB). The results showed that the fluidity of CPB enhanced by RTPF decreased with the increase in fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…The main components waste tire aggregate consists of are the natural and synthetic rubber (also known as a polymer). The styrene-butadiene in the synthetic rubber ratio influences the properties of the polymer: with high styrene content, the rubbers are harder and less rubbery, and takes a longer time to dissolve under normal conditions, which leads to a rise in environmental concern when it ends life service [ 17 , 18 , 19 , 20 , 21 ]. Currently, the worldwide growth of the automobile industry and the increase in car use have tremendously boosted tire production.…”
Section: Introductionmentioning
confidence: 99%